2011
DOI: 10.1002/asna.201011486
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of u ‐, g ‐, r ‐, i ‐, and z ‐band luminosity distributions between galaxy members of compact groups and isolated galaxies

Abstract: Comparisons of u-, g-, r-, i-, and z-band luminosity distributions between galaxy members of compact groups and isolated galaxies Key words galaxies: fundamental parameters -galaxies: statisticsTo investigate the environmental dependence of u-, g-, r-, i-, and z-band luminosities, we perform comparative studies of luminosity distributions between galaxy members of compact groups (CGs) and isolated galaxies. It is found that for the r, i, and z bands isolated galaxies have a higher proportion of faint galaxies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…As it was shown in Table 1 of Deng (2012), in the apparent-magnitude limited Main galaxy sample of the SDSS, the KS probability of different luminosities in subsamples with a redshift bin size of ∆z = 0.01 is fairly small in the redshift region 0.02 ≤ z ≤ 0.10, except KS probability of g-band luminosity. Deng & Zou (2011) also found that KS probability of g-band luminosity is much higher than that of other band luminosities, and argued that this may be due to having different trends in different luminosity regions. Overall, the result of Deng (2012) showed that the environmental dependence of galaxy luminosities is very strong in the redshift region 0.02 ≤ z ≤ 0.10.…”
Section: Statistical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As it was shown in Table 1 of Deng (2012), in the apparent-magnitude limited Main galaxy sample of the SDSS, the KS probability of different luminosities in subsamples with a redshift bin size of ∆z = 0.01 is fairly small in the redshift region 0.02 ≤ z ≤ 0.10, except KS probability of g-band luminosity. Deng & Zou (2011) also found that KS probability of g-band luminosity is much higher than that of other band luminosities, and argued that this may be due to having different trends in different luminosity regions. Overall, the result of Deng (2012) showed that the environmental dependence of galaxy luminosities is very strong in the redshift region 0.02 ≤ z ≤ 0.10.…”
Section: Statistical Resultsmentioning
confidence: 99%
“…The luminosity-environment relation of galaxies has been the subject widely focused on Hamilton 1988;White et al 1988;Loveday et al 1995;Guzzo et al 1997;Willmer et al 1998;Norberg et al 2001Norberg et al , 2002Zehavi et al 2002;Blanton et al 2003Blanton et al , 2005Hogg et al 2003;Berlind et al 2005;Zandivarez et al 2006;Park et al 1994Park et al , 2007Deng et al 2007aDeng et al , 2008aDeng et al ,b, 2009aDeng et al , 2012aDeng 2012;Deng & Zou 2011, 2014a. In the local Universe, many authors found that galaxy luminosity has a strong environmental dependence: luminous galaxies show a tendency to reside in dense environments, while faint galaxies tend to reside in low density regions (e.g., Park et al 1994;Norberg et al 2001;Blanton et al 2003Blanton et al , 2005Zandivarez et al 2006;Deng et al 2007aDeng et al , 2008aDeng et al ,b, 2009a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the local three-dimensional galaxy density (Galaxies Mpc −3 ) that defined as the number of galaxies (N = 5) within the three-dimensional distance to the 5th nearest galaxy to the volume of the sphere with the radius of this distance, in two volume-limited Main galaxy (Strauss et al 2002) samples of the SDSS DR10 (Ahn et al 2014), Deng (2014) found that old galaxies exist preferentially in the dense regions, while young galaxies are located preferentially in low density regions. Deng (2015aDeng ( , 2015b) also reported that stellar velocity dispersion and K-band luminosity of Main galaxies shows substantial correlation with the local environment, respectively.…”
Section: Introductionmentioning
confidence: 95%